Molecular dissection of the response of a rice leucine-rich repeat receptor-like kinase (LRR-RLK) gene to abiotic stresses - Park, SeoJung (Journal of plant physiology, 2014)
Copyright © 2014 Elsevier GmbH. All rights reserved.